Can the federal and state government sue an individual for defamation? - Shair Mohamad, Mohd Akram; Kamarudin, Abdul Rani (Lexis Nexis, 2017)
Defamation's purpose is to protect one's reputation from harm where a statement is published which refers to them and would lower their reputation in the minds of right-thinking members of society. Defamation takes two forms: slander which is a transitory statement, or libel, which is a statement in permanent form. Reflecting the fact that this permanence means that the statement is easily disseminated and the damage in terms of the reputation to the person intended tends to be permanent there is no requirement in libel to prove that damage did occur. This is further justified based on the difficulties of an individual establishing that the loss of reputation was due to the statement, as a reputation is the soul of an individual. The rule applies to all plaintiffs regardless of their nature. However, the first successful challenge to this well-established principle was made in the English apex court in the landmark case of Derbyshire County Council v Times Newspaper Limited and Others [1993] 1 All ER 1011. It was held that any government institution (local or central) could not bring a defamation action. To have held otherwise would have been fundamentally at odds with the public interest, as defamation claims could be used to censor criticism and stifle free speech. In a democracy, governmental bodies should be subject to criticism: otherwise, weaknesses or wrongdoings on the part of the political parties with the mandate to govern will not come to light, and voters during the election may not be able to make an informed choice who they should vote for. The 'chilling' effect of libel claims may prevent matters of public importance coming to light. The Derbyshire principle was applied in Malaysia in two High Court cases. On appeal, the decision in the first case was affirmed in 2015. The decision in the second case was reversed in April 2016, a majority decision where the court refused to accept the Derbyshire common law principle on the grounds that the political system is not the same as England, and that there are already in existence express statutory provisions allowing the state or central government to sue anyone for libel. This article discusses the state of the law on this crucial subject by analysing the rational underlying the common law embodied in the Derbyshire principle, and whether it should or should not be received in Malaysia in the light of conflicting judicial decisions in Malaysia.